STROKE IN PATIENTS WITH TANDEM LESIONS: WHAT IS THE CLINICAL SIGNIFICANCE AND SAFETY OF EMERGENT REVASCULARIZATION OF THE EXTRACRANIAL INTERNAL CAROTID ARTERY? - Coelho, Andreia (2017)
Acute ischemic stroke as a result of tandem occlusion, is defined as a combination of internal cervical carotid artery (ICA) stenosis with synchronous intracranial thrombus and accounts for about 10–20% of all strokes. Nevertheless, their approach remains controversial and variable according to the center's experience. The aim of any stroke treatment must be to successfully revascularize as soon as possible. In tandem occlusion, the primary cause of symptoms and clinical outcome is thrombus in the intracranial arteries rather than the occlusion of the cervical ICA. Today, standard of care for such intracranial lesions is mechanical thrombectomy with stent retriever combined with thrombolysis. However, distal access is hampered by the ICA stenosis/occlusion. The objective of this review was to evaluate the clinical importance and risks associated with emergent revascularization of the internal carotid artery using angioplasty and stenting in tandem occlusions. With this purpose a revision of existing literature was performed using Medline database. Surpassing an extra-cranial ACI lesion with subsequent stent placement seems to have a high recanalization rate, but it is time-consuming, thus delaying the time for distal recanalization and potentially conditioning less favorable neurological outcomes. In the literature, there is no evidence of patient outcome improvement with emergent stent placement in regard to intracranial recanalization (Thrombolysis in Cerebral Infarction≥2b), clinical outcome (modified Rankin Scale ≤2) and mortality rate at 90 days. Additionally, emergent stent placement exposes the patient to the additional risk of stroke associated with the procedure and intracranial hemorrhage. We therefore conclude that currently, there is no evidence in the literature to support emergent carotid stenting in stroke due to tandem occlusions.